2021
DOI: 10.21468/scipostphys.10.5.100
|View full text |Cite
|
Sign up to set email alerts
|

The Loschmidt Index

Abstract: We study the nodes of the wavefunction overlap between ground states of a parameter-dependent Hamiltonian. These nodes are topological, and we can use them to analyze in a unifying way both equilibrium and dynamical quantum phase transitions in multi-band systems. We define the Loschmidt index as the number of nodes in this overlap and discuss the relationship between this index and the wrapping number of a closed auxiliary hypersurface. This relationship allows us to compute this index systematically, using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In the Hermitian case, the quantum metric [58] is a gauge invariant and measurable quantity [59][60][61] that can be seen as a momentum-space Riemannian metric. [62][63][64][65] It has been shown that g 𝜇𝜈 plays a central role in Chern insulators, [66][67][68][69] spreading of the Wannier functions, [70] superconducting weight in flatband superconductors, [71][72][73][74] topological semimetals, [75][76][77][78] quantum phase transitions [79][80][81] and in the semiclassical equations for wave-packets. [82] Moreover, the non-Hermitian version of the quantum metric has been originally introduced in Ref.…”
Section: Band Geometry and Topology For Dcbmentioning
confidence: 99%
“…In the Hermitian case, the quantum metric [58] is a gauge invariant and measurable quantity [59][60][61] that can be seen as a momentum-space Riemannian metric. [62][63][64][65] It has been shown that g 𝜇𝜈 plays a central role in Chern insulators, [66][67][68][69] spreading of the Wannier functions, [70] superconducting weight in flatband superconductors, [71][72][73][74] topological semimetals, [75][76][77][78] quantum phase transitions [79][80][81] and in the semiclassical equations for wave-packets. [82] Moreover, the non-Hermitian version of the quantum metric has been originally introduced in Ref.…”
Section: Band Geometry and Topology For Dcbmentioning
confidence: 99%
“…where ”, Îœ = q, p. It may be meaningful that the Fubini-Study metric is intimately related to the Berry curvature through a quantum geometric tensor (QGT) [40][41][42][43].…”
Section: Dgcmmentioning
confidence: 99%
“…When the phase driving parameter is quenched across an underlying equilibrium phase transition point, a series of zero points of LE emerge at some critical times. In general, exact zeros of LE only occur when the system size tends to infinity 1,23,24 . Meanwhile, LE always approaches to zero in the thermodynamical limit even when the quench parameter does not cross the transition point.…”
Section: Introductionmentioning
confidence: 99%